SOFTWARE QUALITY ANALYSIS USING THE ISO 25010:2011 STANDARD ON THE ONLINE SINGLE SUBMISSION SYSTEM - Tri Kusuma Wardhani; Ihsan Jatnika; Suryarini Widodo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The analysis conducted on software quality uses the ISO 25010:2011 standard on the Electronically Integrated Business Licensing System which is useful for calculating the quality of software produced by a company that meets the requirements set by the world standard body, namely, ISO. This study uses the usability characteristics contained in the ISO 25010:2011 standard. The stages carried out in the analysis of software quality in the licensing system are trying to be integrated electronically using the Analytical Hierarchy Process (AHP) method, an assessment of six sub-characteristics of usability, namely appropriateness recognizability, learnability, operability, user error protection, user interface aesthetics and accessibility. The testing of the licensing system is trying to be integrated electronically using a questionnaire using the J.R Lewis method, with 19 questions. The test results on the appropriateness recognizability sub-characteristics got a value of 1.504, the learnability sub-characteristic got a value of 0.776, the operability sub-characteristic got a value of 0.688, the user error protection sub-characteristic got a value of 0.82, the user interface aesthetics sub-characteristic got a value of 0.255, accessibility sub characteristics get a value of 0.215. The total results of the six sub-characteristics obtained a value of 4.258, from 5 indicators of achievement and feasibility of test results, with the total criteria of test results ranging from 4.10 to 5.00 with very good information, it can be concluded that the overall licensing system is trying to be integrated electronically capable of carrying out all functions and capabilities that are available, effective and efficient in use, and have reliability on the user's side.